Non-unions after intramedullary nailing of fractures of the humeral diaphysis - Veselý, Radek; Pavlacký, Tomáš; Gajdošíková, Kateřina; Paša, Libor (Úrazová chirurgie, 2018)
Aim of the work: The aim of this work is to evaluate the results of the treatment of the non-unions of humeral diaphysis after primary intramedullary nailing. Material and method: From January 2010 to January 2017, 209 patients with fractures of the humeral diaphysis with an intramedullary nail were operated at the Trauma Hospital in Brno. The group involved retrospectively evaluated patients with a nonunion of humeral diaphysis originated after primary treatment of fracture with an intramedullary nail These nonunions were treated by nail extraction and stabilization by autocompression or LCP. The shortest follow-up period of the patients after nonunion surgery was at least 12 months. Evaluated criteria of the group of non-unions included primary fracture types, types of nonunions, Constant shoulder score, disabilities of the arm, shoulder and hand (DASH) score, bone healing time after revision surgery and possible complications. Results: 14 patients were included in the group of patients with nonunion following primary intramedullary osteosynthesis of the humeral diaphysis fracture addressed by nail extraction and splint stabilization. In all patients, the nail was primarily inserted in the antegrade procedure. The mean follow-up after the revision surgery was 26 months. Eight cases were hypertrophic, two in oligotrophic and in four patients arthophic. The healing of the nonunion occurred in all operated patients in an average period of 4.1 months. The DASH score was 13 points at the end of the follow-up of the group of revision surgeries. Constant shoulder score was 77 points on average. After the revision surgery, 3 patients had transient paresis of the radial nerve. In two cases, nerve function was fully restored. In one case, distal forearm and hand hyperaesthesia persist. Conclusion: Fractures of type A1 and B1 according to the AO classification appear to be predisposed for the possible development of nonunion. The solution of each nonunion should be approached individually with good preoperative planning.
Keywords: fraktury humeru; Treatment Outcome; Retrospective Studies; Fracture Fixation, Intramedullary; Postoperative Complications; lidé; intramedulární fixace fraktury; Humeral Fractures; Risk Factors; Pseudarthrosis; reoperace; diafýzy; Female; výsledek terapie; Diaphyses; Reoperation; Male; ženské pohlaví; Humans; mužské pohlaví; pseudoartróza; rizikové faktory; pooperační komplikace; retrospektivní studie